Groundwater isotope ratios reflect convective and stratiform (paleo)precipitation fractions in Brazil - Chang, Hung K. [UNESP]; Gonçalves, Roger D. [UNESP]; Aggarwal, Pradeep K.; Stradioto, Marcia R. [UNESP]; Hespanhol, Emilio C.B. [UNESP]; Sturchio, Neil C.; Romatschke, Ulrike; Araguas, Luis J.A. (Elsevier, 2020)
The stable isotope ratios of oxygen and hydrogen in shallow groundwater reflect the long-term amount-weighted mean isotopic composition of precipitation. Here, we report the isotopic composition of more than 1000 shallow groundwater samples (age < ∼5,000 yr) across continental Brazil. Recent studies of global precipitation have shown a strong negative correlation between the isotopic compositions (e.g., δ18O values) and stratiform fractions of Brazilian precipitation, with geospatial correspondence to the South Atlantic convergence zone pattern. This isotope-precipitation type geospatial correlation is also reflected in the isotopic compositions of shallow groundwaters, and speleothem records from the region show small variations in δ18O values, implying general climatic stability in this region during the past few millennia. We propose that shallow groundwater isotopic compositions reflect bulk proportions of convective and stratiform fractions in precipitation and could thus be useful in conjunction with groundwater dating as proxy archives to characterize past changes in the proportions of convective and stratiform precipitation in tropical and subtropical latitudes. This groundwater isotope-precipitation type relationship could also have broader implications when considered for paleoclimatic interpretation of oxygen isotope records in dated speleothems from other locations.
Keywords: Convective and stratiform precipitation; Groundwater isoscape; South atlantic convergence zone; Speleothems; Stable isotopes